Management of unusually presenting open pelvic and bilateral femur fractures with crush injury of a foot in an adolescent: A case report - Pandey, Nitesh Raj; Poudel, Arjun; Rajbhandari, Ansul; Banskota, Ashok Kumar; Banskota, Bibek (Nepal Orthopaedic Association Journal, 2025)
BACKGROUNDThis case outlines the management of a challenging case involving an adolescent patient presenting with open pelvic fracture, bilateral femur fractures and crush injury to the foot. The treatment approach integrates stage wise surgical interventions, wound care, and rehabilitation strategies to address each injury aspect systematically. Emphasis is placed on early stabilization, meticulous wound management, and coordinated multidisciplinary care to optimize functional recovery and minimize complications.